Prototipe Monitoring Kualitas Udara Ruangan Berbasis Awan Adafruit SGP30 Air Quality Sensor - Kusumah, Hendra; Handayani, Indri; Susilo, Prabowo (Technomedia Journal, 2018)
We usually spend about 70-90% of our time indoors. This project raises awareness about how important it is to open the existing window in the room periodically and allow fresh air to enter. In the room it is very influential in the comfort of doing various activities. Almost all the rooms we visit are offices and restaurants using Air Conditioner (AC). Most AC users leave the AC room still alive. Air conditioning is one of the electronic goods that uses a large wattage and is a very waste of electrical energy, resulting in a very large effect on the increase in electricity costs and electricity payments. This must be considered by the building owner to monitor the condition of the parts of the room, so that the use of electrical energy in each room is more efficient without reducing the comfort of the room user. In this study a monitoring design was carried out which aimed to monitor the condition of several rooms using particles and Ubidots. From a web-based monitoring system, it has managed to find out how much temperature and humidity of a room, as well as the security that is seen from the amount of smoke content detected by the SHT31-D Temperature & Humidity Sensor. This monitoring system can be very useful for housing, restaurant, or office building that has a large number of rooms with high activity. Keywords: Temperature, Humidity, Gas Sensors, Air Quality